2001
DOI: 10.1093/ajcn/74.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Pork with a high content of polyunsaturated fatty acids lowers LDL cholesterol in women

Abstract: Consumption of pork with a high PUFA content resulted in a decrease in the subjects' total plasma and LDL cholesterol and shifted the fatty acid composition from SFAs to PUFAs in the plasma and erythrocytes. Modification of the fatty acid composition of animal foods will be a useful approach to lowering the saturated fat consumption of Americans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 45 publications
0
22
0
2
Order By: Relevance
“…Few studies investigated the health effects of livestock products. The nutritional composition of monogastric animal source foods has been shown to be sensitive to feeding practices (26), and this may have an effect on health (27).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies investigated the health effects of livestock products. The nutritional composition of monogastric animal source foods has been shown to be sensitive to feeding practices (26), and this may have an effect on health (27).…”
Section: Discussionmentioning
confidence: 99%
“…Lipids were extracted, extracts were dried under N 2 and saponified, and the fatty acids were methylesterified (30). Fatty acids were separated by GLC (41) and are presented as a percentage of total fatty acid content.…”
Section: Animals and Dietsmentioning
confidence: 99%
“…For example, Stewart et al (2001) reported that pork containing high levels of polyunsaturated fatty acids lowered low density lipoprotein cholesterol in women compared with pork with a more traditional fatty acid content. It has been recommended that fat in the human diet be made up of a polyunsaturated to saturated (P:S) fatty acid ratio of 1:1 (Grundy et al 1982).…”
mentioning
confidence: 99%